2014
DOI: 10.4103/1658-354x.136435
|View full text |Cite|
|
Sign up to set email alerts
|

Pain relief in day care arthroscopic knee surgery: A comparison between intra-articular ropivacaine and levobupivacaine: A prospective, double-blinded, randomized controlled study

Abstract: Background:Post-operative pain frequently hampers implementation of day care arthroscopic knee surgery in spite of so many analgesic, local anesthetic drugs and routes of administration.Aims:The aim of the present study was carried out to compare the efficacy of ropivacaine and levobupivacaine when administered through intra-articular route in controlling pain after day care arthroscopic knee surgery.Setting and Design:It was a prospective, double-blinded and randomized controlled study.Materials and Methods:A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Our study was supported by the study by Das et al Das et al found that intra-articular levobupivacaine increases the duration of analgesia and decreases the need for rescue analgesic in first postoperative 24 hrs. [10] ElHamamsy et al compared inta-articular dexmedetomidine and fentanyl with bupivacaine 0.25% in a volume of 30 ml. They concluded that both dexmedetomidine and fentanyl in combination with bupivacaine resulted in increased time to first analgesic request and decreased the need for postoperative analgesia as well as increased the duration of pain relief as compared with bupivacaine alone.…”
Section: Resultsmentioning
confidence: 99%
“…Our study was supported by the study by Das et al Das et al found that intra-articular levobupivacaine increases the duration of analgesia and decreases the need for rescue analgesic in first postoperative 24 hrs. [10] ElHamamsy et al compared inta-articular dexmedetomidine and fentanyl with bupivacaine 0.25% in a volume of 30 ml. They concluded that both dexmedetomidine and fentanyl in combination with bupivacaine resulted in increased time to first analgesic request and decreased the need for postoperative analgesia as well as increased the duration of pain relief as compared with bupivacaine alone.…”
Section: Resultsmentioning
confidence: 99%
“…Intra-articular route of drug administration is an example for the management of pain after joint surgery utilizing the peripheral receptors [3]. Different authors in their previous studies with intraarticular ropivacaine [1,15], fentanyl [16], dexmedetomidine [11], levobupivacaine, and morphine [17] proved their efficacy in providing post-operative analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Its association with varying amounts of pain postoperatively, even in less complex procedures such as diagnostic arthroscopy or arthroscopic meniscectomies, is a concern though [1,2]. The hypothesized reason being irritation at the free nerve endings of synovial tissue and anterior pad of fat during surgical excision and resection [3]. Undoubtedly, post-operative pain which is poorly controlled often has an unfavorable impact on the patient's psychology causing discomfort, dissatisfaction, and hampering early ambulation and thus discharges from the hospital [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations